Tumor cell-released autophagosomes (TRAPs) promote immunosuppression through induction of M2-like macrophages with increased expression of PD-L1. Issue 1 (18th December 2018) - Wen, Zhi-Fa; Liu, Hongxiang; Gao, Rong; Zhou, Meng; Ma, Jie; Zhang, Yue; Zhao, Jinjin; Chen, Yongqiang; Zhang, Tianyu; Huang, Fang; Pan, Ning; Zhang, Jinping; et al.
Abstract : Background: Tumor-associated macrophages (TAMs) facilitate tumor progression via establishment of an immunosuppressive tumor microenvironment (TME). However, it is poorly understood how tumor cells could functionally modulate TAMs. Our previous work indicated that tumor cell-released autophagosomes (TRAPs), a type of LC3-II + double-membrane extracellular vesicles (EVs) was sufficient to suppress anti-tumor immune responses by inducing IL-10-producing B cells and immune suppressive neutrophils. Here, we hypothesized that TRAPs may participate in regulating macrophage polarization. Methods: TRAPs isolated from multiple murine tumor cell lines and pleural effusions or ascites of cancer patients were incubated with bone marrow-derived macrophages (BMDMs) and monocytes, respectively. Cellular phenotypes were examined by flow cytometry, ELISA and quantitative PCR. TRAPs treated BMDMs were tested for the ability to suppress T-cell proliferation in vitro, and for promotion of tumor growth in vivo. Transwell chamber and neutralization antibodies were added to ascertain the inhibitory molecules expressed on BMDMs exposed to TRAPs. Knockout mice were used to identify the receptors responsible for TRAPs-induced BMDMs polarization and the signaling mechanism was examined by western blot. Autophagy-deficient tumors were profiled for phenotypic changes of TAMs and IFN-γ secretion of T cells by flow cytometry. The phenotype of monocytes from pleural effusions or ascites of cancer patients was assessed by flow cytometry. Results: TRAPs converted macrophages into an immunosuppressive M2-like phenotype characterized by the expression of PD-L1 and IL-10. These macrophages inhibited the proliferation of both CD4 + and CD8 + T cells in vitro, and promoted tumor growth mainly through PD-L1 in vivo. TRAPs-induced macrophage polarization was dependent on TLR4-mediated MyD88-p38-STAT3 signaling. In vivo studies indicated that disruption of autophagosome formation in B16F10 cells by silencing the autophagy gene Beclin1 resulted in a remarkable delay in tumor growth, which was associated with reduced autophagosome secretion, TAMs reprogramming and enhanced T cell activation. Moreover, the levels of LC3B + EVs appeared to correlate significantly with up-regulation of PD-L1 and IL-10 in matched monocytes from effusions or ascites of cancer patients, and TRAPs isolated from these samples could also polarize monocytes to an M2-like phenotype with increased expression of PD-L1, CD163 and IL-10, decreased expression of HLA-DR, and T cell-suppressive function. Conclusions: These findings suggest the TRAPs-PD-L1 axis as a major driver of immunosuppression in the TME by eliciting macrophage polarization towards an M2-like phenotype, and highlight the potential novel therapeutic approach of simultaneously targeting autophagy and PD-L1.